Sustainable Model of Organic Agriculture: A Case study of Nepalese Farmers - Banjara, Raj Kumar; Poudel, Meena (Journal of Advanced Academic Research, 2017)
Epistemology of organic agriculture is logically and practically associated with the conventional farming practices. Organic agriculture can contribute in the social life of people by improving health and ecology. It is even more important for the preservation of natural resources. In relation to the importance of organic agriculture, the main objective of this study was to develop the sustainable model of organic agriculture. The study was based on the inductive approach; qualitative design. Study was conducted in 4 districts of Nepal among the 614 respondents. The result found that there was significant contribution made by the organic agriculture to improve the socio-economic status of farmers as well as to care the relationship between the human being and their environment. Family farming system is the fundamental base for changing trend of agriculture in worldwide practices. There is need to protect and enhance family farming through farmers’ cooperative for the sustainability of organic agriculture. The study developed the sustainable model covering the need of infrastructure development, policy improvement, and motivational factors for farmers and changing process of modern agriculture to organic agriculture. The roles of government, non-government, private sectors, individual farmers and consumers are equally important for the sustainability of organic agriculture. The model focuses on the collective effort of all responsible stakeholders. There is need to test the effectiveness of this model.